Managerial ownership and firm performance in Thailand: An empirical analysis - Singhchawla, Wanachan; Evans, Robert; Evans, John (Virtus Interpress, 2010)
This study investigates whether managerial share ownership serves to enhance or detract from firm performance in listed companies in Thailand. The convergence-of-interest hypothesis asserts that firm value increases as management ownership rises. On the other hand, when managers own a substantial fraction of the firm shares, then voting power or other influence may satisfy other non-value-maximising objectives without endangering other positions. This gives rise to the entrenchment hypothesis, which suggests the excessive insider ownership has negative impact on corporate performance. The results of this study support both the alignment and entrenchment efforts and therefore the existence of a non-linear relationship between firm performance and managerial ownership. Firm size and industry are also shown to impact significantly on firm performance in Thailand.